OPPRESSION AGAINST WOMEN IN ADRIENNE SHELLY'S WAITRESS (2007): A FEMINIST APPROACH - EDI, HARJUNA (2010)
The major problems of this study is oppression against women in the household being reflected in Adrienne Shelly Waitress. The aims of the study are to analyze the film based on the structural elements and to analyze the film based on the feminist theory. In analyzing Waitress movie, the writer uses the qualitative method and Feminist Perspective. The data sources are primarily data source, which uses the Waitress script written by Adrienne Shelly in 2007, and secondary data source is biography, an essay, comment, historical information and other relevant informations. The method of collecting data is library research. The technique for analyzing is descriptive analysis. The outcomes of the study show the following conclusions. Firstly, based on the structural analysis, it indicates that each of narrative and technical element of movie have been related into solid unity. Secondly, based on Feminist analysis, it depictes oppression againts women in household. The last, the author wants to assert that everybody has strength and weakness regardless the power to be someone he or she wants.